Using the UBPR method Unified Banking Performance Reports - in measuring the performance of Iraqi commercial banks - Abdul Aziz Shuwaish Abdul Hamid Al-Jubouri (Iraqi Journal for Administrative Sciences, 2025)
This research related to a new method for evaluating banks performance that are called (Uniform Bank Performance Reports).This method is used in U.S.A by some governmental agencies that interested in controlling the banking system there. These reports regards as analytical tool used to control banks and to examine its performance. It shows the controller the effect of management decisions and economic conditions on bank performance, with respect to earnings, liquidity, capital adequacy , asset-liabilities management, which gives the management of the bank and the controlling agencies best understanding and more clear glance to the financial position of the bank that is evaluated. The way of preparing these reports is based on grouping included identical banks in groups according to some criteria ( as the volume of assets, capital, or the year of establishment, or any criterion that assigned by the examiners then to use uniform measurement to evaluate these banks by financial ratios or by sums and to compare them with the peer group that the bank lies in. This approach can give a more clear view about the bank when it compared according to uniform criteria in a framework that contains all banks that are peer to it. The research contains the assessment of the problem which represented with the fact that the performance evaluation process in Iraqi banking system is very weak. And to show the importance of this process to the banking system. then to review the (UBPR) method and its component . and to examine it( according to the available data) on some Iraqi banks after dividing them on peer groups Including governmental banks as the first group. And the private banks that divided in tow groups according to its capital. Then the Arab and foreign banks as the last group. Then to test the results to know the usefulness of its usage according to the conditions of Iraqi banks , the information that are available about them and the level of disclosure by them. The research ended with some conclusions and recommendations.